Interplay between genetics and environment in an Andean tree species - Sekely, Jill (2021)
Environmental conditions exert major selective pressures on local plants and are one of the main drivers of local adaptation patterns. Identifying specific effects of individual environmental factors including temperature, precipitation, and day length on the genotypes of local trees is one of the main foci of modern forest genetics. However, disentangling individual effects in situ is often complicated by landscape autocorrelation and overlapping environmental gradients. A native temperate tree species that inhabits the Argentine Andes, Nothofagus pumilio, presents an ideal in situ study scenario because the southern Andes run almost perfectly north-to-south over the species? continuous 2000-kilometer range. The naturally narrow and linear species distribution follows clear latitude, elevation, and environment gradients, which allow us to examine patterns of local adaptation and identify loci that may be under environmental selection. We used a paired sampling site study design with high and low elevation sites, as well as dry and wet elevation sites. We performed targeted sequencing on 497 adult trees from 20 sampling sites along the entire species range. We used the resulting SNP set to analyse the population genetic structure to determine general patterns of species-wide and subpopulation genetic variation, relatedness, and expansion following the last glacial maximum. We also performed genotype environmental associations using interpolated climactic information (CHELSAcruts dataset) to identify putative SNPs under selection and determine potential climatic drivers of selection. These results will inform and fuel further downstream analyses of local adaptation within our project, including GWAS and gene flow analyses.